Experiences and management strategies of Norwegian GPs during the COVID-19 pandemic: a longitudinal interview study - Silje Rebekka Heltveit-Olsen; Lene Lunde; Anja Maria Brænd; Ivan Spehar; Sigurd Høye; Ingmarie Skoglund; Pär-Daniel Sundvall; Guro Haugen Fossum; Jørund Straand; Mette Bech Risør (Taylor & Francis Group, 2023)
AbstractObjective When the COVID-19 pandemic reached Norway, primary health care had to reorganize to ensure safe patient treatment and maintain infection control. General practitioners (GPs) are key health care providers in the municipalities. Our aim was to explore the experiences and management strategies of Norwegian GPs during the COVID-19 pandemic - over time, and in the context of a sudden organizational change.Design Longitudinal qualitative interview study with two interview rounds. The first round of interviews was conducted from September-December 2020, the second round from January-April 2021. In the first interview round, we performed eight semi-structured interviews with GPs from eight municipalities in Norway. In the second round, five of the GPs were re-interviewed. Consecutive interviews were performed 2-4 months apart. To analyze the data, we used thematic analysis.Results The COVID-19 pandemic required GPs to balance several concerns, such as continuity of care and their own professional efforts. Several GPs experienced challenges in the collaboration with the municipality and in relation to defining their own professional position. Guided by The Norwegian Association of General practitioners, The Norwegian College of General Practice and collegial support, they found viable solutions and ended up with a feeling of having adapted to a new normal.Conclusions Although our study demonstrates that the GPs adapted to the changing conditions, the current municipal health care models are not ideal. There is a need for clarification of responsibilities between GPs and the municipality to facilitate a more coordinated future pandemic response.Key PointsFacing the COVID-19 pandemic, the primary health care service in Norway had to reorganize to ensure safe patient treatment and maintain infection control.Several GPs experienced challenges in collaboration with the municipalities.There is a need for clarification of responsibilities between GPs and the municipality.